Epidemiological Profile of Surgically-Treated Peripheral-Nerve Diseases - Fuzari, Helen Kerlen Bastos; Andrade, Armèle Dornelas de; Souza, Renata Janaina Pereira de; Bernardino, Silvya Nery; Souza, Fernando Henrique Moraes de; Sarmento, Antonio; Oliveira, Daniella Araújo de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Objective To outline the epidemiological profile of surgical patients treated at the peripheral-nerve outpatient clinic of a public hospital in the state of Pernambuco, Brazil, from 2008 (the year this service was implemented in the hospital ) to 2016.Material and Methods A cross-sectional study with data collection from the medical records. A descriptive analysis was performed with the qualitative variables presented as relative and absolute frequencies, and the quantitative variables, as means and standard deviations. The studied variables were gender, age, diagnosis, and surgical techniques.Results In total, 506 medical records were analyzed. Of these, 269 were of male patients (53%), and 238 were of female patients (46%). The age of the sample ranged from 5 to 84 years (41 ± 14 years). The most prevalent diagnoses were: carpal tunnel syndrome (38.9%) followed by traumatic brachial plexus injury (33.2%). The first diagnosis was more frequent among women, while the second, among men. This collaborates with the predominant findings of upper-limb lesions (91%), in which men accounted for 52,75% (244) and women, for 47,25% (217).Conclusion The present study provided relevant information regarding the reality of peripheral-nerve surgeries performed at a public hospital in the state of Pernambuco, Brazil. Public health issues increasingly require the continuity of public policies and government incentive.
Keywords: epidemiology; brachial plexus; carpal tunnel syndrome